Elemental Distributions in Marine Sediments in the Straits of Melaka Using Neutron Activation and Mass Spectroscopic Analyses - Al-Zahrany, Awad Ahmed (2006)
The horizontal and vertical distributions of concentrations of major, minor, and trace elements from the grap and core marine sediment samples along the West Coast of Peninsular Malaysia were investigated. All together there are 35 elements including the following 27 elements namely Al, As, Br, Ca, Ce, Co, Cr, Cs, Eu, Fe, Hf, K, La, Lu, Mg, Mn, Na, Rb, Sb, Sc, Sm, Ta, Th, U, V, Yb, and Zn were studied by using Instrumental Neutron Activation Analysis (INAA) and the following 8 elements namely Cd, Cu, Mo, Pb, Ni, Sr, Ba, and Ti were studied by using Inductively Coupled Plasma-Mass Spectroscopy (ICP-MS) technique. The obtained elemental concentrations were evaluated by various methods including by comparing the concentrations to that of the mean crustal materials and average shales, the national studies, and the international guidelines for marine sediments of Canada, Netherlands and USA-New York State. The enrichment factor method was used to determine whether the elements belong to anthropogenic and non-anthropogenic sources. In addition, different statistical analysis methods including the linear regression analysis and the cluster analysis were used to determine the correlation of concentrations between the measured elements. To ensure the accuracy and precision of the generated data, proper quality control and quality assurance procedures have been incorporated in the INAA analysis including ‘blank’, duplicate sample analysis, application of certified reference materials, and quantification using K0-NAA procedure. The data generated using ICP-MS were subject to the same quality control and quality assurance procedures as the INAA analysis without K0-NAA procedure. For the horizontal elemental distributions the grab sediment samples were used. The non-anthropogenic elements identified by the enrichment factor calculation were Al, Ba, Ca, Cd, Co, Cr, Cu, K, Mg, Mn, Mo, Na, Ni, Rb, Sr, Ta, Ti, V, and Zn. The concentrations of Al, Ba, Cd, Co, Cr, Cu, K, Mn, Mo, Ni, Sr, Ta, Ti, V, and Zn are lower than those of the average shales and the mean crustal materials. This may be due to high solubility of these elements in the tropical weathering. The concentrations of Ca, Mg and Na are lower than the mean crustal materials but higher than the average shales. The concentration of Rb is slightly greater than that of the mean crustal materials but lower than the average shales. Also, this may be due to high solubility of Ca, Mg, Na, and Rb in the tropical weathering. The anthropogenic elements in the grab sediment samples were As, Br, Cs, Fe, Hf, Pb, Sb, Th, and U. The concentrations of As, Br, Cs, Hf, Pb, and Sb are greater than those of the mean crustal materials. This indicates that there were external inputs of anthropogenic sources such as industrial and mining activities at the inland area along the Straits of Melaka. The concentration of Pb is approximately twice of the average shales and three times than the mean crustal materials. Higher concentration of Pb in the grab sediment samples may be due to industrial activities such as manufacture of batteries and automotive emissions from cities along the rivers flowing into the Straits of Melaka. For the vertical elemental distributions the core sediment samples were used. The non-anthropogenic elements Al, Ba, Cd, Co, Cr, Cu, Fe, K, Mg, Mn, Mo, Na, Ni, Rb, Sr, Ta, Ti, V, and Zn in the core sediment samples are lower than the concentrations of the mean crustal materials and average shales. The anthropogenic elements in the core sediment samples were As, Br, Ca, Cs, Hf, Pb, Sb, Th, and U, where the concentrations of Br, Ca, Cs, Hf, Th, and U are greater than the concentrations of the mean crustal materials and average shales. This indicates that there were external inputs of anthropogenic sources such as industrial and mining activities at the inland area along the Straits of Melaka. The concentration of Pb is greater than the concentration of the mean crustal materials but lower than the average shales. For toxic elements such as As, Cd, Cr, Cu, Fe, Mn, Ni, Pb, Sb, and Zn the mean concentrations are either lower than or equal to the mean concentrations for the Straits of Johor and the Penang Island. Moreover, the mean concentrations of most elements were found lower than the international guidelines for marine sediments from Canada, Netherland and USA-New York State, except for the concentrations of Cr and Ni, which are greater than the international guidelines. The depth profile of As/Al, Cd/Al, Cr/Al, Cu/Al, Fe/Al, Mn/Al, Sb/Al, and U/Al of the core sediment samples normalized to aluminum metal revealed the general trends that the concentration level in the upper layer is higher than the bottom layer. The explanation for the higher concentrations of As, Cd, Cr, Cu, Fe, Mn, Sb, and U in the upper layers may be due to the lower oxygen level in an anoxic sediment which caused digenesis process in which the multi-oxidations state in those elements tend to be higher for concentration level at the surface sediment layer. This indicates that the core marine sediments in the Straits of Melaka are having enough oxygen level and remain healthy for marine ecosystem.